Does Arterialization of Portal Vein Have Any Effects in Large-for-Size Liver Transplantation? Hemodynamic, Histological, and Biomolecular Experimental Studies. Issue 6 (1st June 2022) - Torres, Rafael Rodrigues; Tannuri, Ana Cristina Aoun; Serafini, Suellen; Belon, Alessandro; Gonçalves, Josiane Oliveira; Loreto, Celso di; Tannuri, Uenis
Abstract: Background: In pediatric liver transplantation, the optimal size of the transplanted liver ranges between 0.8% and 4.0% of the recipient's weight. Sometimes, the graft weight exceeds this upper limit, characterizing the large-for-size condition potentially associated with reduced blood flow and worsening of ischemia-reperfusion injury. Therefore, it would be beneficial to increase the portal flow through arterialization of the portal vein. Materials and methods: Fifteen pigs underwent large-for-size liver transplants. They were divided into two groups: control (CTRL 6 animals – conventional technique) and arterialization – a shunt was established between the portal vein and the splenic artery (ART 9 animals). Hemodynamic, biochemical, histological, and molecular variables were compared. Results : Arterialization resulted in a significant increase in portal vein pressure but no changes in other hemodynamic variables, as shown in the analysis of variance. It was observed lower ALT values ( p  = 0.007), with no differences regarding the values of blood pH and lactate ( p  = 0.54 and p  = 0.699 respectively) or histological variables (edema, steatosis, inflammation, necrosis, and IRI – p  = 1.0, p  = 0.943, p  = 0.174, p  = 0.832, p  = 0.662, respectively). The molecular studies showed significantly increased expression of IL6 after 3 hours of reperfusion ( p  = 0.048) and decreased expression of ICAM immediately after reperfusion ( p  = 0.03). The regression analysis suggested a positive influence of portal flow and pressure on biochemical parameters. Conclusion : Arterialization of the portal vein showed no histological, biochemical, or molecular benefits in large-for-size transplantation.